Effect of anesthetic, analgesic and sedative agents on human cell phagocytosis. Review. / - Mosquera, Jesús; Pimienta, Ivan (Investigación Clínica, 2020)
Abstract. Along with preoperative stress, anesthetics per se are associated with decreased activity of the immune system. Phagocytosis is an important process where particles, such as dead cells and bacteria, are eliminated from the organism. This process is complex and involves cell chemotaxis, tissue infiltration, several coordinated cellular events and the production of reactive oxygen and nitrogen species (ROS). Therefore, the aim of this review was to report the effects of anesthetic, analgesic and sedative agents on human cell phagocytosis. This review suggests that human phagocytosis processes are affected by main anesthetic, analgesic and sedatives agents that result in decreased chemotaxis, phagocytosis and ROS production. These effects may impair the anti-bacterial function of phagocytes. Clinical anesthesiologists should select the anesthetics and the anesthetic methods with careful consideration of the clinical situation and the immune status of patients, concerning long-term mortality, morbidity, and the optimal prognosis. Resumen. La anestesia y el estrés preoperatorio están asociados a la depresión del sistema inmunitario. La fagocitosis es un proceso importante destinado a la eliminación de células muerta y microorganismos. Es un proceso complejo que involucra la quimiotaxis celular, la infiltración tisular leucocitaria y la activación de diversos procesos intracelulares coordinados, que incluyen la producción de especies reactivas de oxígeno y nitrógeno (ERON). Por lo tanto, el propósito de esta revisión fue reportar el efecto de agentes anestésicos, analgésicos y sedativos en la fagocitosis humana. Esta revisión sugiere que los procesos relacionados con la fagocitosis humana son afectados por los principales agentes anestésicos, analgésicos y sedativos, que inducen una disminución de la quimiotaxis, fagocitosis y producción de ERON y la función anti-bacterial de los fagocitos. Los anestesiólogos clínicos deben seleccionar los anestésicos y los métodos de anestesia, considerando la situación clínica y el estado inmunitario de los pacientes en relación a la mortalidad, morbilidad y pronóstico óptimo a largo plazo.